Discrepancies in corporate GHG emissions data and their impact on firm performance assessment - Georgios Papadopoulos (European Commission, 2022)
Corporate greenhouse gas (GHG) emissions data underpin almost every economic analysis related to climate change, spanning from firms' transition risk to their ESG ratings and, ultimately, their reduction is fundamental in addressing global warming. However, various quality issues plague relevant data. This study documents the scale of discrepancies in GHG emissions data among three commercial data providers along various dimensions, investigates the reasons behind these and examines the possible ramifications for assessing firms' environmental performance. It finds widespread inconsistencies between data providers in every emissions category, through time and across sectors. The lowest -yet important- inconsistencies are observed in direct emissions data (Scope 1) and they progressively increase in indirect emissions (Scope 2 and Scope 3). A sectoral analysis reveals specific sectors with higher levels of inconsistencies. A detailed investigation shows that inconsistencies originate from a few, common sources, mostly related to the nature of emissions disclosure requirements. Finally, a simple ranking exercise exhibits that these inconsistencies can translate into diverging carbon performance assessments.
Keywords: 330